PENAMBAHAN BRAIN GYM PADA CORE STABILITY EXERCISE LEBIH MENINGKATKAN KESEIMBANGAN DINAMIS ANAK USIA 7-8 TAHUN DI PPA TUNAS KASIH ABIANBASE - Ni Putu Dwi Larashati; Ni Wayan Tianing; I Made Muliarta (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACT Nowadays, decreasing of physical activity of children were increasing the risk of falling and injury. Physical activity will increase the balancing ability and reduced risk of fall. Development of dynamic balance started at age 7 to 8 years. This study was an experimental study with pre test and post test control group design involving 14 children in Group I (brain gym and core stability exercise) and 14 children in Group II (core stability exercise). Results of Wilcoxon Signed Rank Test found a significant difference with p=0.001 (p<0.05) in Group I and Group II. Different test difference with Mann Whitney U-Test showed a significant difference between Group I and Group II where p=0.001 (p<0.05), the conclusion is brain gym in core stability exercise is more effective in increasing the dynamic balance among children 7 to 8 years old in PPA Tunas Kasih Abianbase than core stability exercise only. Keywords: brain gym, core stability exercise, dynamic balance